Tessituras de memoriais de formação com coordenadoras pedagógicas: reflexões sobre os processo formativos - Adriana Mota Ivo Martins (2022)
This research emphasizes the theme of training pedagogical coordinators. It metaphorically considers the writing of a text as a seam, in which the researcher experiences a process of basting the stitches made between the theoretical-methodological assumptions and listening to the participants. The study is based on the (auto)biographical perspective (Passeggi, 2010; 2013; 2019; Bolívar, 2002). The concepts of coordination and training were discussed and re-signified based on the concepts of Araújo (2007); Franco (2014); Freire (2015) and Nóvoa (2021). Thus, the research aimed to understand the trajectories of the pedagogical coordinators, based on the construction of Training Memorials in Reflective Groups, highlighting the training and self-training processes. Nine (9) meetings were held with nine (9) pedagogical coordinators from the Belo Horizonte Municipal Education Network (RME/PBH). The interpretative analysis used was the densification of text meanings, inspired by Jovchelovitch and Bauer (2002). The educational resource (e-book) was produced with the participants and shows the process of reconstruction of the training experiences by the coordinators. The results reveal the need to think about training at school and the process of training coordinators considering: a) the mediating and research function of coordination; b) a training methodology that values problematization, reflection on the lived experience, exchanges between peers, listening and looking at oneself; c) the need for cohesive training proposals in training concepts and forms of mediation for all segments involved; e) Training Memorials and Reflective Groups of Biographical Mediation as research and training devices, enabling dialogue and narrative reflexivity.